CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS FOR PARKINSONISM AND PARKINSON'S DISEASE IN KRASNODAR REGION - D. K. Sichinava; L. I. Bonzyuk; E. A. Kurynnaya; M. A. Barabanova (Инновационная медицина Кубани)
Parkinson’s disease and parkinsonism are very socially significant as they impact life quality (early disability, noticeable kinetic and cognitive deteriorations). In this article we described incidence rate of Parkinson’s disease and parkinsonism, special features of medical care for patients with Parkinson’s disease in Krasnodar region.